Developing Skills for Economic Transformation and Social Harmony in China: A Study of Yunnan Province - Liang, Xiaoyan (World Bank, 2015)
The World Bank has a long history of investing in China?s technical and vocational education and training (TVET), dating back to the 1963 Higher Education Project, which benefited selected tertiary TVET programs in project schools. The initial World Bank projects for TVET in China were designed mostly on the national level, supporting selected institutions in multiple provinces.